2016
DOI: 10.1245/s10434-016-5561-0
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Invasion is a Major Prognostic and Predictive Factor of Response to Adjuvant Chemotherapy in Stage I–II Colon Cancer

Abstract: PNI a major prognostic and predictive factor in stage II colon cancer, and our results support the use of adjuvant chemotherapy in patients with PNI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 49 publications
10
42
0
Order By: Relevance
“…Molecular features of tumors are generally used to guide decision making for adjuvant chemotherapy in patients with stage II disease, although evidence supporting this practice is still weak [35][36][37][38][39][40][41][42][43][44][45]. In most countries (including Taiwan), the most common, reliable, and affordable methods of determining risk features are examinations of high-risk clinicopathologic features and the tumor, node, and metastasis (TNM) stage [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular features of tumors are generally used to guide decision making for adjuvant chemotherapy in patients with stage II disease, although evidence supporting this practice is still weak [35][36][37][38][39][40][41][42][43][44][45]. In most countries (including Taiwan), the most common, reliable, and affordable methods of determining risk features are examinations of high-risk clinicopathologic features and the tumor, node, and metastasis (TNM) stage [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the potential predictive role of perineural invasion and microsatellite instability in disease progression and for chemotherapy benefit for patients with stage II CRC, but no definite conclusive statements have been made due to limited supporting data [22,23]. Epithelial-mesenchymal transition (EMT) as an oncogenic molecular event has been extensively investigated in the CRC field during the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…However, overemphasis on LNM in the colon cancer TNM staging system is controversial. Many studies have reported the prognostic impact of high-risk features beyond LNM [11][12][13][14][15][16][17][18][19][20][21][22][23]. One study showed the relationship between the number of high-risk features and prognosis, demonstrating that 5-year OS rate was less than 20% in patients with stage II colon cancer with four or more high-risk features [18].…”
Section: Discussionmentioning
confidence: 99%